2013
DOI: 10.4319/lo.2013.58.3.0921
|View full text |Cite
|
Sign up to set email alerts
|

Physical responses of small temperate lakes to variation in dissolved organic carbon concentrations

Abstract: We used a mechanistic physical model to examine the effect of variability in dissolved organic carbon (DOC) concentrations on the physical properties of small temperate lakes. The model was validated on eight small (6 3 10 24 to 3.8 3 10 22 km 2 ) lakes in Wisconsin and Michigan, with a standard error , 1uC for seven of eight lakes. Attenuation of photosynthetically active radiation (400-700 nm) in these lakes was regulated by DOC concentrations and was important in the vertical structuring of water temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 37 publications
14
164
2
Order By: Relevance
“…Under these conditions, we measured the extracellular carbon release by phytoplankton and directly determined the BR, as these are the key variables implied in the ratio of bacterial carbon demand to C supply. Moreover, since a strong feedback between physical processes (e.g., mixing, stratification) and changes in DOC concentration in small lakes has previously been reported (Read and Rose, 2013), we further achieved an advance in our knowledge by investigating two oligotrophic ecosystems that differed in their UVR penetration in the water column due to their DOC content, selected as model lakes representing two ends of an optical gradient of transparence to UVR in Mediterranean inland waters. This provides a framework for disentangling the complex processes that underlie biological interactions under changing physical (stratification, UVR) and chemical (DOC) conditions, which can then modify the C flux in aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, we measured the extracellular carbon release by phytoplankton and directly determined the BR, as these are the key variables implied in the ratio of bacterial carbon demand to C supply. Moreover, since a strong feedback between physical processes (e.g., mixing, stratification) and changes in DOC concentration in small lakes has previously been reported (Read and Rose, 2013), we further achieved an advance in our knowledge by investigating two oligotrophic ecosystems that differed in their UVR penetration in the water column due to their DOC content, selected as model lakes representing two ends of an optical gradient of transparence to UVR in Mediterranean inland waters. This provides a framework for disentangling the complex processes that underlie biological interactions under changing physical (stratification, UVR) and chemical (DOC) conditions, which can then modify the C flux in aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…East of the Appalachians receives more precipitation; changes in the delivery of this surface or groundwater flow may be critical factors influencing deepwater temperature in this region, as has been observed in a deep, tropical lake [62]. In small, sheltered, but stratified lakes where wind mixing is minimal, water transparency may be a key modifier of deepwater trends [22,57,60]. Low water transparency limits heat penetration and restricts transfer of thermal energy to deeper waters [56]; however, in this study, transparency was not a clear driver of deepwater trends as a whole ( Figure 5).…”
Section: Deepwater Trendsmentioning
confidence: 99%
“…Water transparency can control near-surface temperature trends through controlling vertical light absorption at the surface [56]. For example, less transparent lakes could have increased rates of surface absorption and outgoing radiation, especially at night [57], which would lead to decreasing surface warming trends, a rare occurrence in NENA lakes. Additionally, sunlight can only warm a fraction of the mixed layer in less transparent lakes [47], which limits light and heat penetration to sub-surface layers.…”
Section: Near-surface Warmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, GLEON science has demonstrated that the choice of physical model can have a large and significant influence on estimates of gas exchange across lakes spanning a productivity gradient , in some cases resulting in a switch from a lake being considered net autotrophic versus heterotrophic. Regarding the important role of lakes and reservoirs in the global carbon cycle, variation in dissolved organic carbon among lakes can help explain their thermal responses to external energy inputs (Read and Rose 2013) and has important implications for how lakes respond as sentinels of climate change (Williamson et al 2014, O'Reilly et al 2015. While dozens of papers using more than one lake can be cited within the GLEON context, the aforementioned studies exemplify the collaborative nature of GLEON through data sharing (http://gleon.org/data).…”
Section: Comparative Studiesmentioning
confidence: 99%